Passive Two-Camera System to Generate a Depth Map of a Scene and Depth Estimation using Optical Flow Techniques. - Lee, Sooyong (Universiti Teknologi Petronas, 2003)
This paper presents a method to recover depth information from a 2-D image taken from different viewpoints. An implementation of a passive two-camera system and a regionbased matching algorithm implemented in Matlab generates a depth map of a scene based on a pair of stereo images. Matlab scripts implementing optical flow algorithms were written. The optical flow for a motion sequence was computed and the vector field that shows both the direction and magnitude of the corresponding motion displayed.